The Use of Role Play Technique in Teaching Speaking at Senior High School - Anna Husna (Pencerah, 2025)
This study which used library research is intended to look some theories and research findings related to the use of role play in teaching speaking. It is difficult for students to convey the idea in English due to lack of vocabulary, idea, self-confidence, and motivation. To solve the problems, the teacher should apply an appropriate technique to improve student’s speaking skill. In this research, the writer recommends role play technique. Role play is a technique which can develop students’ fluency in target language, promote students’ speaking skill or interact with each other in classroom, increase motivation and make the teaching learning process more enjoyable. The study shows that using role play technique is effective in improving the students’ speaking skill and students’ self-confidence. This study is expected to be useful for English teachers in teaching speaking, and students can also be motivated in learning and developing their speaking skill effectively.